Sistema para gerenciamento do carregamento de baterias alimentado por uma turbina eólica - Farias, Guilherme de Carvalho (2016)
This study consists in a comparative analysis of MPPT strategies for low power wind turbines and the development of a control methodology for a battery charging system. The main MPPT strategies in the literature are described and implemented, along with all of their auxiliary control loops. To perform the comparison, a simulation platform is developed. Mathematical modeling of all components in the platform is described, as well as how they relate with each other. This platform allows keeping the system parameters the same for all methods, and modifying only the necessary to implement each of them. The control method for battery charging is presented and analyzed. One of the MPPT strategies described is applied together with this methodology. The methodology of the simulations are performed with switched models to validate the project realized with the developed average models.